On new strong versions of Browder type theorems (2018)
An operator T acting on a Banach space X satisfies the property (UWπ) if σa(T)\σSF-+ (T) = π (T), where σa(T) is the approximate point spectrum of T, σSF-+ (T) is the upper semi-Weyl spectrum of T andπ (T) the set of all poles of T. In this paper we introduce and study two new spectral properties, namely (Vπ) and (Vπa ), in connection with Browder type theorems introduced in [1], [2], [3] and [4]. Among other results, we have that T satisfies property (Vπ) if and only if T satisfies property (UWπ) and π (T) = σa(T).